A kind of injectable Angelica sinensis polysaccharide(ASP)/hydroxyapatite (HAp) material for bone tissue engineering promoting vascularization, hematopoiesis, and osteogenesis in mice. Issue 4 (4th March 2018) - Zhang, Weijie; Zhao, Lei; Ma, Jianzhong; Yang, Chenguang; Wang, Xiaochun; Pu, Xiuying; Wang, Yonggang; Ran, Fen; Wang, Yanling; Ma, Hui
ABSTRACT: Scaffolds made from single hydroxyapatite (HAp) possess neither biological properties of bone nor functions of promoting vascularization and inhibiting immune rejection. To overcome these drawbacks of HAp, Angelica sinensis polysaccharide (ASP)/HAp composite scaffolds were prepared and its application possibility in bone tissue engineering was studied. The scaffolds were examined by mechanical test, releasing test, degradation test, and histological evaluation. The results showed that the scaffolds had good degradation and ASP releasing. The histological examination indicated that ASP/HAp material could effectively promote vascularization, hematopoiesis, and osteogenesis in mice. In conclusion, the composite material could be used for bone tissue engineering with good prospect. GRAPHICAL ABSTRACT: